Whole exome sequencing revealed variants in four genes underlying X-linked intellectual disability in four Iranian families: novel deleterious variants and clinical features with the review of literature - Atefeh Mir; Yongjun Song; Hane Lee; Hossein Khanahmad; Erfan Khorram; Jafar Nasiri; Mohammad Amin Tabatabaiefar (BMC, 2023)
Abstract Aim and Objective Intellectual disability (ID) is a heterogeneous condition affecting brain development, function, and/or structure. The X-linked mode of inheritance of ID (X-linked intellectual disability; XLID) has a prevalence of 1 out of 600 to 1000 males. In the last decades, exome sequencing technology has revolutionized the process of disease-causing gene discovery in XLIDs. Nevertheless, so many of them still remain with unknown etiology. This study investigated four families with severe XLID to identify deleterious variants for possible diagnostics and prevention aims. Methods Nine male patients belonging to four pedigrees were included in this study. The patients were studied genetically for Fragile X syndrome, followed by whole exome sequencing and analysis of intellectual disability-related genes variants. Sanger sequencing, co-segregation analysis, structural modeling, and in silico analysis were done to verify the causative variants. In addition, we collected data from previous studies to compare and situate our work with existing knowledge. Results In three of four families, novel deleterious variants have been identified in three different genes, including ZDHHC9 (p. Leu189Pro), ATP2B3 (p. Asp847Glu), and GLRA2 (p. Arg350Cys) and also with new clinical features and in another one family, a reported pathogenic variant in the L1CAM (p. Glu309Lys) gene has been identified related to new clinical findings. Conclusion The current study's findings expand the existing knowledge of variants of the genes implicated in XLID and broaden the spectrum of phenotypes associated with the related conditions. The data have implications for genetic diagnosis and counseling.